(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2026)
Background Q-switching is a laser technique that temporarily stores energy in the laser medium before releasing it all at once to produce extremely brief, intense light pulses. "Q" stands for the optical cavity’s quality factor, which is a gauge of how effectively it stores energy. When using Q-switching, the cavity’s Q is initially kept low to avoid lasing as the population inversion increases. The stored energy can then be released in a strong pulse that is frequently nanoseconds long but has peak powers thousands of times higher than continuous wave output when the Q is abruptly switched to high. Objective The Co-ZnFe₂O₄ nanostructur is synthesis by pulsed laser ablation in liquid (PLAL) method, It is then mixed with the previously prepared Rhodamine B dye to boost optical absorption efficiency. Materials Uniform, surfactant-free nanoparticles are produced using a Q-switched Nd:YAG laser (1064 nm, 300 mJ). UV-Vis spectroscopy verified that the resultant nanocomposite showed increased absorption in the visible range when combined with Rhodamine B, exhibiting a discernible redshift in the absorption peak. demonstrating effective energy transfer and robust dye nanoparticle interactions. Results highlight the potential of Rhodamine B–Co-ZnFeO₄ nanostructures for high-performance uses in photocatalysis, optical sensing, and solar energy harvesting. Conclusion Our research shows that PLAL is a quick, easy, and efficient way to customize nanomaterials with exceptional optical qualities.